2014
DOI: 10.1142/s0218810414300058
|View full text |Cite
|
Sign up to set email alerts
|

Dupuytren's Contracture: Emerging Insight Into a Viking Disease

Abstract: Dupuytren's disease is a fibroproliferative condition of the palm, with a predilection for men, which has affected Northern Europeans since the Viking conquests. Although strongly heritable, clear evidence exists for environmental factors that modify the underlying genetic risk, such as diabetes, heavy drinking, and smoking. Evidence also exists for epilepsy (probably due to treatment with certain anti-epileptic drugs), and Human Immunodeficiency Virus infection. Recent large studies have shown no relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Presumably, the primary diagnosis in these patients causes changes at the molecular level that make their fibroblasts susceptible to triggers that initiate dedifferentiation into myofibroblasts, which, consequently, stimulates an imbalance in collagen turnover that leads to nodules, cords, and contractures. 13) Notable distinctions in the presentation of Dupuytren's disease have been observed between diabetic and non-diabetic patients, namely that patients with DM tend to have a milder form of the disease, more commonly have involvement of the middle and ring fingers (as opposed to the ring and small fingers, which is more typical for non-diabetics), and may develop Dupuytren's disease through a different pathophysiologic process. 14,15) Most of the extant literature evaluates the prevalence of Dupuytren's disease among patients with DM, but does not examine the surgical outcomes in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, the primary diagnosis in these patients causes changes at the molecular level that make their fibroblasts susceptible to triggers that initiate dedifferentiation into myofibroblasts, which, consequently, stimulates an imbalance in collagen turnover that leads to nodules, cords, and contractures. 13) Notable distinctions in the presentation of Dupuytren's disease have been observed between diabetic and non-diabetic patients, namely that patients with DM tend to have a milder form of the disease, more commonly have involvement of the middle and ring fingers (as opposed to the ring and small fingers, which is more typical for non-diabetics), and may develop Dupuytren's disease through a different pathophysiologic process. 14,15) Most of the extant literature evaluates the prevalence of Dupuytren's disease among patients with DM, but does not examine the surgical outcomes in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Dupuytren disease most commonly affects men of northern European white descent 21 . A study of a 5‐generation Swedish family suggested that Dupuytren disease is inherited as an autosomal dominant condition with incomplete penetrance 22 .…”
Section: Genetic Links For Development Of Peyronie’s Disease and Dupumentioning
confidence: 99%
“…Several studies have implicated the TGFβ and WNT pathways as drivers of fibrosis in DD (reviewed in [1517]). Expression analyses in DD (by e.g.…”
Section: Molecular and Cellular Alterations In Dd Degenerationmentioning
confidence: 99%